Footprints of Immune Cells in the Pancreas in Type 1 Diabetes; to “B” or Not to “B”: Is That Still the Question? - Leete, Pia; Morgan, Noel G. (Frontiers in Endocrinology, 2021)
Significant progress has been made in understanding the phenotypes of circulating immune cell sub-populations in human type 1 diabetes but much less is known about the equivalent populations that infiltrate the islets to cause beta-cell loss. In particular, considerable uncertainties remain about the phenotype and role of B-lymphocytes in the pancreas. This gap in understanding reflects both the difficulty in accessing the gland to study islet inflammation during disease progression and the fact that the number and proportion of islet-associated B-lymphocytes varies significantly according to the disease endotype. In very young children (especially those <7 years at onset) pancreatic islets are infiltrated by both CD8+ T- and CD20+ B-lymphocytes in roughly equal proportions but it is widely held that the CD8+ T-lymphocytes are responsible for driving beta-cell toxicity. By contrast, the role played by B-lymphocytes remains enigmatic. This is compounded by the fact that, in older children and teenagers (those ≥13 years at diagnosis) the proportion of B-lymphocytes found in association with inflamed islets is much reduced by comparison with those who are younger at diagnosis (reflecting two endotypes of disease) whereas CD8+ T-lymphocytes form the predominant population in both groups. In the present paper, we review the current state of understanding and develop a proposal to stimulate further discussion of the roles played by islet-associated B-lymphocytes in human type 1 diabetes. We cite evidence indicating that sites of direct contact can be found between CD8+ and CD20+-lymphocytes in and around inflamed islets and propose that such interactions may be important in determining the efficiency of beta cell killing.